PENGEMBANGAN MEDIA MONOPOLI BERBASIS LOCAL WISDOM UNTUK MENINGKATKAN LITERASI BUDAYA SISWA SEKOLAH DASAR - Velda Artha Djaya; Yasir Arafat; Murjainah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aimed to develop a local wisdom-based Monopoly learning media to improve the cultural literacy of elementary school students. The study was motivated by the low level of students’ cultural literacy and the limited use of innovative learning media in teaching local culture. This research employed the Plomp development model, which consists of three phases: preliminary research, prototyping stage, and assessment phase. The subjects of the study were fourth-grade students of SD Negeri 23 Talang Kelapa. Data were collected through interviews, questionnaires, and tests. The research instruments included material and media expert validation sheets, teacher and student response questionnaires, as well as pretest and posttest questions. Data were analyzed using percentage techniques and the N-Gain test. The results showed that the local wisdom-based Monopoly media was highly feasible for use in learning, as evidenced by the material expert validation score of 98% and the media expert validation score of 98%, both categorized as “Highly Feasible.” The media was also highly practical, with one-to-one evaluation results of 97%, small-group evaluation results of 85%, and teacher response results of 89%, yielding an overall average of 90%. Furthermore, the media was effective in improving students’ cultural literacy, as indicated by an average N-Gain score of 0.7811 (78.10%), which falls into the high category. Therefore, the local wisdom-based Monopoly media is feasible, practical, and effective for enhancing elementary school students’ cultural literacy on local wisdom materials.